SISTEM PELAYANAN ADMINISTRASI REKAM MEDIK RAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) POSO - Fadlun, Fadlun (Katalogis, 2017)
This study aimed to determine and to analyze the administrative services of inpatient medical records at Poso General Hospital, referring to the opinion of Haryadi (2009: 6) comprising the activities of receiving, processing, storing, presenting information, and treating or maintaining patient medical records. This research was descriptive qualitative. Based on the results of data collection, it was concluded that in general the activities of receiving, processing, storing, presenting information, and treating or maintaining patient medical records had been implemented in accordance with the provisions. However, there were still delays in the medical records services during inpatients examination by physicians. The problem laid on the not-timely change system of duty medical officers, especially for patients entering at night. Medical records frequently could not be found because the duty medical officers accompanying the physicians did not know where the medical records were kept by the duty medical officers before. Additionally, the problems of low education and employment status of the honorary employees influenced the discipline and work behavior of the duty medical officers.